Review of The Institutional View on The Liberalization and Management of Capital Flows. (Policy Papers; Policy Paper, 2022)
The Institutional View (IV) on the Liberalization and Management of Capital Flows, adopted in 2012, provides the basis for consistent advice, and where relevant, assessments on policies related to capital flows. This paper reviews the IV, informed by advances in research, notably the work on an Integrated Policy Framework (IPF), the findings of the 2020 evaluation by the Independent Evaluation Office (IEO) on IMF Advice on Capital Flows, and staff's experience with the implementation of the IV. The core premises and objectives of the IV remain unchanged. The IV rests on the premises that capital flows are desirable as they can bring substantial benefits for countries, and that capital flow management measures (CFMs) can be useful in certain circumstances but should not substitute for warranted macroeconomic adjustment. With those premises in mind, the IV aims to help countries reap the benefits of capital flows, while managing the associated risks in a way that preserves macroeconomic and financial stability and does not generate significant negative outward spillovers.